COMPARING THE FUNCTIONAL OUTCOME OF DIFFERENT DOSE REGIMES OF SUCCINYLCHOLINE WHEN USED FOR RAPID INDUCTION AND INTUBATION - Ahmad, Munir; Khan, Nadeem Ahmad; Furqan, Aamir (Journal of Ayub Medical College Abbottabad, 2018)
Background: To compare outcomes of different doses of succinylcholine, in terms of intubation condition, onset of action, duration of action and abdominal fasciculation. Methods: Thus randomized control trial was conducted in the department of anaesthesia and ICU, Nishter Hospital Multan from April 2016 to November 2016. A total number of 60 patients with ASA status I and II were enrolled. All patients were divided into three groups by lottery method. Data was entered and analysed by computer software SPSS version 23.2. Descriptive variables like age and onset of action were presented as mean and SD and continues statistics like gender, abdominal fasciculation and incubation condition were presented as frequency and percentages. Chi square test and one-way ANOVA was applied to see effect modification and significance of results. The p-value 0.05 was considered as significant. Results: A Total number of 60 patients included in this study and all were female. The mean age of the patients was 28.15±4.5 years. The main outcome variables of this study were the fasciculation, satisfactory intubation, onset time (seconds) and duration of action (in minutes). In group (A) 1mg, Abdominal fasciculation was found 80%, 85% and 75% in group A, B, C respectively. It was also observed that satisfactory intubation was found 90%, 80% and 30% in three groups respectively. The mean onset time was 50.95±4.6, 70.7±5.66 and 94.15±8.73 seconds in three groups respectively. Similarly, the mean duration of action was 16.1±3.76, 13.55±3.01 and 8±2.05 minutes respectively. Conclusion: Results of our clinical trial suggest that succinylcholine in low doses shorter duration of action and low rate of abdominal fasciculation which is desirable for rapid induction but onset of action is prolonged and intubation conditions were not satisfactory predominantly. So, we concluded that low doses of succnylcholine are not so much beneficial that I can replace full doses of succinylcholine when used for rapid induction and intubation. Keywords: Succinylcholine, Rapid induction, Intubation, Anaesthesia